Post-colonial theory and English literature : a reader - Childs, Peter (Edinburgh University Press, 1999)
Unlike other readers, this book takes eight important literary texts and provides some of the most significant post-colonial readings of them published in the last fifteen years. Topics include cannibalism, slavery, the harem, missionary work, gender, nationalism and the Rushdie affair. The book offers practical examples of applying theoretical arguments to specific texts. Key features: * Provides three or four cutting edge essays on each of the following texts: Shakespeare's The Tempest; Defoe's Robinson Crusoe; Bronte's Jane Eyre; Kipling's Kim, Conrad's Heart of Darkness; Joyce's Ulysses; Forster's A Passage to India; Rushdie's The Satanic Verses